Marine algae of St Martin’s Island, Bangladesh. XI. Red Algae (Rhodophyceae) - Aziz, Abdul; Rahman, Md Towhidur (Bangladesh Journal of Botany, 2011)
Falkenbergia hillebrandii (Bornet) Falkenberg, Gelidiella tenera (J. Ag.) Schmitz, Halymenia floridana J. Ag., Liagora harveyiana Zeh and Polysiphonia harveyi Bailey of Rhodophyceae have been recorded and described for the first time from the St Martin’s Island, Cox’s Bazar, Bangladesh. Key words: Seaweeds; Rhodophyceae; St. Martin's Island; Bangladesh DOI: 10.3329/bjb.v39i2.7302 Bangladesh J. Bot. 39(2): 161-168, 2010 (December)